The Effect of Job Placement and Job Loyalty on Employee Performance at the Palembang District Attorney's Office - Diah Maya Sari; Marlina Widiyanti; Muhammad Yusuf; Agustina Hanafi (Journal of Management, Economic, and Financial, 2024)
This study aimed to investigate the impact of job placement and job loyalty on employee performance at the Palembang State Attorney's Office. The research background indicates that effective human resource management, including proper job placement and fostering job loyalty, is essential for organizational success, especially in law enforcement agencies where performance directly affects public service delivery. The population comprised all 134 employees at the office. The sample was selected using purposive sampling, excluding Echelon III (Head of the District Attorney), Echelon IV (Head of Section), and Echelon V (Head of Affairs) positions, as these are determined by the Attorney General's Office of Indonesia. The respondents included 117 employees in functional and executive roles. Multiple linear regression analysis revealed that both job placement and job loyalty positively and significantly affect employee performance. It is recommended that job placement be evaluated to ensure alignment with employees' educational levels. Additionally, while loyalty to work is essential, not all tasks require teamwork. The Palembang State Prosecutor's Office is encouraged to provide job-specific training to enhance employee performance. The study concludes that optimizing job placement and encouraging job loyalty can significantly enhance the overall performance of employees, leading to better organizational outcomes.